Application of student worksheet to see understanding mathematical concepts & communication skills - Dita Oktavihari; Mohammad Mahfud Effendi; Reni Dwi Susanti (STKIP PGRI Banjarmasin, 2019)
This research is a qualitative descriptive research that aims to see the understanding of concepts and mathematical communication of students with the application of LKM. The subjects of this study were the second-semester students of the Government Science Department, Faculty of Social and Political Sciences, University of Muhammadiyah Malang. Data collection techniques used are observation, testing, and documentation. Analysis of the data used is data reduction, data presentation, and drawing conclusions. The application of student worksheets (LKM) was carried out for 3 meetings in April-May 2019. Based on the research conducted, an average grade of 63.86 was obtained. Researchers divide into 2 groups to facilitate data analysis. Assessment is carried out in accordance with indicators of understanding concepts and mathematical communication. The application of LKM can be done to see the understanding of concepts in students well. This is proven that as much as 62.22% of students are able to improve their understanding of the concept. The questions used in the MFI are essay questions. Essay questions can improve students' mathematical communication skills. It can be seen from the results of student work as much as 62.22% able to answer the essay questions so that they can communicate the concepts that have been taught and present them in the form of mathematical representation.